Виникнення і розвиток економічної освіти в російській імперії кінця XVII-XVIII ст. - Олійник, Ю. О. (НТУ "ХПІ", 2014)
У зв’язку з переходом нашої економіки на ринкові відносини проблема організації економічної освіти не може не брати до уваги вітчизняний історичний досвід. Роль економіки в різних сферах суспільного життя настільки вагома, що зараз вже не викликає сумніву необхідність у викладанні дисциплін економічного циклу учням і студентам, навіть якщо вибір їх майбутньої професії не торкнеться економічної сфери діяльності. На сучасному етапі суспільного розвитку рівень і ступінь важливості підготовки економічно освіченого покоління для всіх галузей народного господарства виявились такими, що зумовили необхідність ретроспективного наукового погляду на економічну освіту.

In connection with the transition of our economy to the market relations, the problem of the organization for economic education cannot but take into account domestic historical experience. The role of the economy in different spheres of public life is so weighty that now there is no doubt the necessity of teaching the disciplines of the economic cycle, pupils and students, even if the choice of their future profession does not affect the sphere of economy activity. At the present stage of social development level and degree of importance of preparing economically educated generation for all branches of national economy are such that there is the necessity retrospective scientific view on economic education, in order to identify the sources of knowledge for future profession in the economic field, its historical and practical importance for society.
The emergence and development of economic education in the Russian Empire in the end of XVII-XVIII centuries
Keywords: комерційна освіта; комерційне училище; купецтво; economic education; commercial education; commercial College